2021
DOI: 10.1093/braincomms/fcab065
|View full text |Cite
|
Sign up to set email alerts
|

Tract-specific MRI measures explain learning and recall differences in multiple sclerosis

Abstract: Cognitive difficulties are common and a key concern for people with multiple sclerosis. Advancing knowledge of the role of white matter pathology in multiple sclerosis-related cognitive impairment is essential as both occur early in the disease with implications for early intervention. Consequently, this cross-sectional study asked whether quantifying the relationships between lesions and specific white matter structures could better explain co-existing cognitive differences than whole brain imaging measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Within each tissue type, changes are heterogenous, with different growth trajectories in different cortical regions and white matter pathways (Lebel et al, 2012; Lebel et al, 2008; Schilling et al, 2022a), and different associations with axonal myelination (Grydeland et al, 2019) and densities (Beck et al, 2021; Cox et al, 2016; Giorgio et al, 2010; Schilling et al, 2022a). These studies have driven hypotheses that aim to relate structure and function and determine structural mediators or cognition (Armstrong et al, 2020; Frangou et al, 2022; Winter et al, 2021), or may serve as a benchmark of normative trajectories that might be used to reveal patterns of abnormal variation or vulnerability in disease and disorder (Bethlehem et al, 2022; Fjell and Walhovd, 2010; Shafer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Within each tissue type, changes are heterogenous, with different growth trajectories in different cortical regions and white matter pathways (Lebel et al, 2012; Lebel et al, 2008; Schilling et al, 2022a), and different associations with axonal myelination (Grydeland et al, 2019) and densities (Beck et al, 2021; Cox et al, 2016; Giorgio et al, 2010; Schilling et al, 2022a). These studies have driven hypotheses that aim to relate structure and function and determine structural mediators or cognition (Armstrong et al, 2020; Frangou et al, 2022; Winter et al, 2021), or may serve as a benchmark of normative trajectories that might be used to reveal patterns of abnormal variation or vulnerability in disease and disorder (Bethlehem et al, 2022; Fjell and Walhovd, 2010; Shafer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Li et al, (2012) found different FA covariance patterns for different segments of the corpus callosum. In support of this point, a recent study found that WM tract metrics of volume and microstructural integrity from specific section of specific tracts, including subsections of the corpus callosum, superior longitudinal fasciculus and the striato-prefrontal and striato-parietal pathways, better predict cognitive test performance than global tractography and lesion measures, and also better than whole tract measures ( Winter et al, 2021 ). This lack of granularity in our data may therefore account for the weak component structure that emerged after rotation.…”
Section: Discussionmentioning
confidence: 90%
“…By producing streamlines-based statistics, tractometry was shown to have satisfactory reproducibility in both healthy subjects and individuals with Parkinson’s disease ( Cousineau et al, 2017 ). A recent study utilized tract-specific MRI measures to investigate the relationship between neuropathology and cognition in MS ( Winter et al, 2021 ). In this study, 40 patients with long-lasting MS were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus impossible to determine if the increase in free water fraction for example is driven by the presence of focal lesions only. In future work, the use of intralesional measures and lesionometry ( Winter et al, 2021 ) would be helpful to better characterize diffusion MRI abnormalities caused specifically by MS focal lesions. It would also be interesting to separate gadolinium-enhancing lesions (considered as “active lesions”) from non-enhancing lesions.…”
Section: Discussionmentioning
confidence: 99%